Tax avoidance and persistence of cash flows: moderating role of firm life cycle - Costa, Fabiano de Castro Liberato; Soschinski, Caroline Keidann; Klann, Roberto Carlos (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Objective: This study aimed to analyze the effect of firm life cycle stages on the relationship between tax avoidance and cash flow persistence in the Brazilian context. Methodology: A multiple linear regression model estimated using the Ordinary Least Squares (OLS) method was employed on a sample of 2,034 observations of Brazilian non-financial firms listed on the stock exchange. The firm life cycle analysis employed the model proposed by Dickinson (2011). Total and Permanent Book-Tax Differences (BTD) were used to measure tax avoidance. Results: The results suggest that tax avoidance is positively related to cash flow persistence, with the growth stage strengthening this relationship, while the maturity and decline stages weaken it. These results highlight that permanent tax strategies are superior to temporary ones in terms of firms’ ability to retain cash. Contributions: This study contributes to the literature by highlighting that temporary and permanent tax reduction strategies present distinct results in terms of their ability to influence future cash flows. While previous research has documented that temporary differences harm earning persistence, this study demonstrated that permanent differences favor cash flow persistence. As a practical implication, the research is useful for investors, analysts, and other users of accounting information, who can appropriately utilize information on tax avoidance and business life cycle in their company valuation models.